A fourth dose of Omicron RBD vaccine enhances broad neutralization against SARS‐CoV‐2 variants including BA.1 and BA.2 in vaccinated mice. Issue 8 (6th May 2022) - Zhou, Bing; Song, Shuo; Guo, Huimin; Zhou, Xinrong; Fan, Qing; Liu, Weilong; Cheng, Lin; Ge, Xiangyang; Ju, Bin; Zhang, Zheng
Abstract: The SARS‐CoV‐2 vaccines have been widely used to build an immunologic barrier in the population against the COVID‐19 pandemic. However, a newly emerging Omicron variant, including BA.1, BA.1.1, BA.2, and BA.3 sublineages,  largely escaped the neutralization of existing neutralizing antibodies (nAbs), even those elicited by three doses of vaccines. Here, we used the Omicron BA.1 RBD as a fourth dose of vaccine to induce potent Omicron‐specific nAbs and evaluated the broadly neutralizing activities against SARS‐CoV‐2 variants. The BA.1‐based vaccine was indeed prone to induce a strain‐specific antibody response substantially cross‐reactive with BA.2 sublineage, and yet triggered broad neutralization against SARS‐CoV‐2 variants when it was used in the sequential immunization with WT and other variant vaccines. These results demonstrated that the booster of Omicron RBD vaccine could be a rational strategy to enhance the broadly nAb response.